(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of Pott’s disease in patients of paraparesis presenting to medical wards of Civil Hospital Karachi. Study Design: Cross sectional study Place and Duration of Study: This study was conducted in all Medical Wards of Civil Hospital, Karachi, from 1st January 2012 to 31 Dec 2012. Material and methods: A total of 133 patients of spastic paraparesis & meeting inclusion criteria were included in this study. Inquiry was carried out regarding age, gender, presenting complaints, duration of illness, past history of TB and site of involvement of spine. Diagnosis of Pott’s diasease was made on Magnetic Resonance Imaging (MRI) findings of soft tissue edema, disc space narrowing, paraspinal mass or vertebral collapse. Results: Out of 133 patients, mean age was 47.7 (±15.6) years with male: Female = 1.6: 1. Out of 133 patients of spastic paraparesis, Pott’s disease was diagnosed in 53 (39.8%) cases. Frequency of pott’s disease was high in male (M: F = 2.1: 1), 36 (43.9%). Average age of patients with pott’s disease was 49 ±13.2 years (Min – Max = 22 – 80 years). Conclusion: In this study Pott’s disease was diagnosed in 39.8% patients of spastic paraparesis. Frequency of pott’s disease was high in male gender and older (Age: 31 – 50 years) patients.